Laboratory Report EEX6450 ANALOG ELECTRONIC SYSTEMS & INSTRUMENTATION Lab 02 By C.J.AMARASINGHE 612265044 Submitted to Department of Electrical and Computer Engineering Faculty of Engineering Technology The Open University of Sri Lanka At Colombo Regional Center DESIGN OF A WIDE BAND AMPLIFIER AIM To design a Wide Band Amplifier OBJECTIVES To become familiar with the procedure of amplifier with emphasis on design consideration at high frequencies APPARATUS Resistors Capacitors Transistors Zener diode DC power supply Oscilloscope Signal Generator THEORY An amplifier is a device where a small input signal is used to control a large output signal. This signal may be current, voltage or power. An amplifier functions by taking power from a power supply and controlling the output to match the input signal shape but with a larger amplitude. In this sense, an amplifier modulates the output of the power supply based upon the properties of the input signal. An amplifier is effectively the opposite of an attenuator: while an amplifier provides gain, an attenuator provides loss. By considering the range of signal frequency over which the amplifier has useful gain amplifiers can be classified as Audio low frequency amplifiers Radio frequency amplifiers Wide band amplifiers DC amplifiers Frequency Response curve: A graph of amplifier gain (in dB) against signal frequency (in logarithmic scale) is called Frequency Response Curve. The basic frequency Response Curve for a Wide band Amplifier is shown in the following graph. CALCULATIONS AC Equivalent Circuit 𝛽 𝛽 𝑅𝜋1 = 𝑔 1 , 𝑅𝑎 = (𝑅1 ∥ 𝑅2 ) ∥ (𝑅𝑓 + 𝑅3 ) 𝑅𝜋2 = 𝑔 2 𝑚1 𝑚2 𝑅𝑥 = 𝑅3 ∥ 𝑅𝑓 𝑅𝑖𝑛2 = 𝑅𝜋2 + (𝛽 + 1)𝑅𝑥 Let 𝑉 𝐾1 = 𝑉2 𝐾2 = 1 𝑉𝑜𝑢𝑡 = 𝑔𝑚2 (𝑉2 − 𝑉3 )𝑅𝐿 𝑉𝑜𝑢𝑡 𝑉2 ------- (1) (𝑉2 − 𝑉3 ) 𝑉3 = [ + 𝑔𝑚2 (𝑉2 − 𝑉3 )]𝑅𝑥 𝑅𝜋2 1 𝑉3 = (𝑉2 − 𝑉3 )[𝑅 + 𝑔𝑚2 ]𝑅𝑥 𝜋2 -------- (2) 𝑉2 = −𝑔𝑚1 𝑉1 (𝑅𝐶 ∥ 𝑅𝑖𝑛2 ) 𝑉2 = −𝑔𝑚1 (𝑅𝐶 ∥ 𝑅𝑖𝑛2 ) = 𝐾1 𝑉1 From equation (2) 1 1 𝑉3 [1 + (𝑔𝑚2 + ) 𝑅𝑥 ] = 𝑉2 [𝑔𝑚2 + ]𝑅𝑥 𝑅𝜋2 𝑅𝜋 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝑉3 𝜋 = = K3 𝑉2 1 + (𝑔 + 1 )𝑅 𝑚2 𝑥 𝑅 𝜋2 𝑉 𝐾3 = 𝑉3 2 From equation (1) 𝑉𝑜𝑢𝑡 = (𝑉2 − 𝑉3 ) 𝑔𝑚2 𝑅𝐿 𝑉3 = 𝑉2 − 𝑉𝑜𝑢𝑡 𝑔𝑚2 𝑅𝐿 By both sides divided by 𝑉2 𝑉𝑜𝑢𝑡 𝑉3 𝑉2 − 𝑔𝑚2 𝑅𝐿 = 𝑉2 𝑉2 By eliminating from K3 𝑉 𝑉2 − 𝑔 𝑜𝑢𝑡 𝑅 𝑚2 𝐿 𝑉2 = 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝜋2 1 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 𝜋2 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝑉𝑜𝑢𝑡 𝜋2 1− = 𝑔𝑚2 𝑅𝐿 𝑉2 1 + (𝑔 + 1 )𝑅 𝑚2 𝑥 𝑅 𝜋2 1− 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝜋2 1 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 = 𝑉𝑜𝑢𝑡 𝑔𝑚2 𝑅𝐿 𝑉2 𝜋2 𝑉𝑜𝑢𝑡 𝑔𝑚2 𝑅𝐿 = = 𝐾2 1 𝑉2 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 𝜋2 𝐴𝑖𝑜𝐿 = 𝑖𝑜𝑢𝑡 −𝑔𝑚2 (𝑉2 − 𝑉3 ) = 𝑉1 𝑖𝑖𝑛 ⁄(𝑅 ∥ 𝑅 ∥ 𝑅 ) 𝑠 𝑎 𝜋1 Using K3 , eliminating V3 from 𝐴𝑖𝑜𝐿 ; −𝑔𝑚2 𝑉2 (1 − 𝐴𝑖𝑜𝐿 = 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝜋2 ) 1 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 𝜋2 𝑉1 ⁄(𝑅 ∥ 𝑅 ∥ 𝑅 ) 𝑠 𝑎 𝜋1 (−𝑔𝑚2 )(−𝑔𝑚2 )(𝑅𝐶 ∥ 𝑅𝑖𝑛2 )(𝑅𝑠 ∥ 𝑅𝑎 ∥ 𝑅𝜋1 ) 1 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 𝜋2 Obtain the transfer function 𝐴𝑖𝑜𝐿 = 𝑉𝑜𝑢𝑡 = −𝑔𝑚2 (𝑉2 − 𝑉3 )(𝑅𝐿 ∥ 1 ) 𝐶3 𝑆 1 ]𝑅 𝑅𝜋 𝑥 1 1+(𝑔𝑚2 + )𝑅 𝑅𝜋2 𝑥 From K3 ; 𝑉3 = 𝑉2 [ [𝑔𝑚2 + ] Converting current source I2 to Voltage source 𝑉3 𝑍1 = ( 𝑍1 = 1 ∥ 𝑅𝑎 ∥ 𝑅𝜋1 ) 𝐶1 𝑆 𝑅𝑎 𝑅𝜋1 𝑅𝑎 + 𝑅𝜋1 + 𝑆𝑅𝑎 𝑅𝜋1 𝐶1 By voltage divider rule 𝑉1 = ( 𝑍1 )𝑉 𝑍1 + 𝑅𝑆 𝑆 Since, 𝑍1 = 𝑅 𝑅𝑎 𝑅𝜋1 𝑎 +𝑅𝜋1 +𝑆𝑅𝑎 𝑅𝜋1 𝐶1 Substituting for 𝑍1 we get, 𝑅𝑎 𝑅𝜋1 𝑅𝑎 + 𝑅𝜋1 + 𝑅𝑎 𝑅𝜋1 𝐶1 𝑆 𝑉1 = [ ]𝑉𝑆 𝑅𝑎 𝑅𝜋1 + 𝑅 𝑆 𝑅𝑎 + 𝑅𝜋1 + 𝑅𝑎 𝑅𝜋1 𝐶1 𝑆 𝑉1 = 𝑅𝑎 𝑅𝜋1 𝑉𝑆 𝑅𝑎 𝑅𝜋1 + 𝑅𝑎 𝑅𝑆 + 𝑅𝑆 𝑅𝜋1 + 𝑅𝑎 𝑅𝜋1 𝑅𝑆 𝐶1 𝑆 Also, 𝑉2 = (𝑍2 ∥ 𝑅𝑖𝑛2 )(−𝑔𝑚1 𝑉1 ) − − − −(3) 1 ; 𝑍2 = 𝑅𝐶 ∥ 𝐶 2𝑆 𝑍2 ∥ 𝑅𝑖𝑛2 = 𝑅𝐶 ∥ 𝑅𝑖𝑛2 ∥ 𝑉2 = 1 𝑅𝐶 ∥ 𝑅𝑖𝑛2 = 𝐶2 𝑆 1 + (𝑅𝐶 ∥ 𝑅𝑖𝑛2 )𝐶2 𝑆 (−𝑔𝑚1 𝑉1 )(𝑅𝐶 ∥ 𝑅𝑖𝑛2 ) 1 + (𝑅𝐶 ∥ 𝑅𝑖𝑛2 )𝐶2 𝑆 − − − − (4) From (3) & (4) 𝑉2 = (−𝑔𝑚1 )(𝑅𝐶 ∥ 𝑅𝑖𝑛2 )(𝑅𝑎 𝑅𝜋1 )𝑉𝑆 [1 + (𝑅𝐶 ∥ 𝑅𝑖𝑛2 )𝐶2 𝑆] [𝑅𝑎 𝑅𝜋1 + 𝑅𝑎 𝑅𝑆 + 𝑅𝑆 𝑅𝜋1 + 𝑅𝑎 𝑅𝜋1 𝑅𝑆 𝐶1 𝑆] From transfer function 𝑉3 𝑅𝐿 𝑉𝑜𝑢𝑡 = −𝑔𝑚2 𝑉2 (1 − )( ) 𝑉2 1 + 𝑅𝐿 𝐶3 𝑆 𝑉𝑜𝑢𝑡 = −𝑔𝑚2 𝑉2 (1 − 1 [𝑔𝑚2 + 𝑅 ]𝑅𝑥 𝑅𝐿 )( ) 1 1 + 𝑅 𝐶 𝑆 𝐿 3 1 + (𝑔𝑚2 + 𝑅 )𝑅𝑥 𝜋2 𝜋 Eliminating 𝑉2 with 𝑉𝑆 , We get 𝑉𝑜𝑢𝑡 𝑉𝑆 = 𝑔𝑚1 𝑔𝑚2 (𝑅𝐶 ∥𝑅𝑖𝑛2 )𝑅𝑎 𝑅𝜋1 𝑅𝐿 1 [1+(𝑔𝑚2 + )𝑅 ] [1+𝑅𝐿 𝐶3 𝑆] 𝑅𝜋2 𝑥 [1+(𝑅𝐶 ∥𝑅𝑖𝑛2 )𝐶2 𝑆] [𝑅𝑎 𝑅𝜋1 +𝑅𝑎 𝑅𝑆 +𝑅𝑆 𝑅𝜋1 +𝑅𝑎 𝑅𝜋1 𝑅𝑆 𝐶1 𝑆] Where the 3 poles in the transfer function ω1 = R a R π1 + R a R S + R 3 R π1 R a R π1 R S C1 ω2 = R C + R in2 R C R in2 C2 ω3 = 1 R L C3 DISCUSSIONS